(untitled) (Asian Education Studies, 2022)
In order to achieve the goal of cultivating professional application-oriented talents in application-oriented colleges and universities, the OBE education concept (Outcomes-based education, outcome-oriented education) can be introduced into the teaching reform practice of real estate development and marketing courses. By summarizing and comparing the differences between the traditional education model and the modern OBE education model, combined with the teachers’ experience and thinking in the process of teaching practice, summed up the problems found in the teaching of the past courses, and finally formed the "OBE concept applied to the real estate development and marketing courses". "Result-oriented, student-centered, continuous improvement" reform ideas and the actual operation process in curriculum practice.